DEMYSTIFYING STUDENT NEEDS IN NON-ENGLISH PROGRAMS FOR ENGLISH-SPECIFIC PURPOSES - Arisandi, Vidya; Sudrajat, Ajat; Yudistira, Daffa Adam; Prakoso, Mohammad Bagas; H.S, Siti Julaeha (TELL - US JOURNAL, 2023)
It cannot be hindered that needs analysis is a crucial element of English for Specific Purposes theory. Without it, effective communication in targeted domains cannot be achieved. Since ESP is linked to their field of study it presupposes that student chose to be extra curious in comprehending issues related to their domain of study or work, which should have a connection between components and English skills. This study examines students' requirements for learning English for specific purposes, encompassing their needs, preferences, and areas of deficiency, with a focus on multidimensional learning needs. The research employs a descriptive qualitative approach. This study employed several techniques to collect data, including conducting interviews with students enrolled in English for Business Management (ESP) courses during their second semester. The results of this research were analyzed using Hutchinson and Waters (1987) theory of needs analysis. Researchers found that students have a high need to learn English; they desire to improve their speaking skills for work, but there is a gap between their current proficiency level and what they need.   It is highly recommended for students who are planning to pursue a degree in management studies to possess an intermediate level of proficiency in the English language before starting their academic journey. Therefore, it is advisable for students in the management study program to have at least an intermediate level of English proficiency before commencing their studies. This strategy ensures their ability to address their English learning requirements effectively.